Análise de regiões intergênicas de escherichia coli utilizando ferramentas computacionais - Klauck, Hugo André (My University, 2019)
Genes are segments of the deoxyribonucleic acid (DNA) molecule that contain information related to the metabolic functions necessary for the survival of an organism. Understanding the mechanisms that regulate gene expression and to identify these factors contributes to the understanding of the function of genes in different species. The gene transcription process begins in bacteria through interactions between RNA polymerase enzyme and specific regions of DNA called promoters, which interact with different factors σ, act as key regulators of gene expression. Bioinformatics through computational tools has contributed generating inferences that help in understanding various biological phenomena, including the prediction of regulatory elements. Similarly, the growth of computational research has generated large amounts of data, requiring computational tools to be adapted for processing and obtaining results. Therefore, the present study was overall objective presented in the form of scientific articles, analysis around computational tools for analysis of intergenic regions of prokaryotes beings. The results show, using intergenic regions extracted from IntergenicDB, (i) verified the performance of computational promoter prediction tools available on the internet, (ii) using computational tools, presents a comparative analysis of intergenic regions of E. coli strains (commensal and pathogenic), relating the structure of the promoters with the pathogenic capacity and (iii) the development of the integration of sequence analysis tools whith IntergenicDB through creating a web service.
Os genes são segmentos da molécula de ácido desoxirribonucleico (DNA) que contém as informações relacionadas às funções metabólicas necessárias para a sobrevivência de um organismo. O entendimento dos mecanismos que regulam a expressão gênica e a identificação destes elementos, contribui para a compreensão da funcionalidade dos genes em diferentes espécies. O processo de transcrição de genes em bactérias se inicia através das interações entre a enzima RNA polimerase e regiões específicas no DNA chamadas promotoras, que interagindo com diferentes fatores σ, agem como reguladores chave da expressão gênica. A bioinformática através de ferramentas computacionais tem contribuído gerando inferências que auxiliam na compreensão de diversos fenômenos biológicos, entre eles a predição de elementos regulatórios, da mesma forma, o crescimento de pesquisas computacionais tem gerado grandes quantidades de dados, exigindo que as ferramentas computacionais estejam adaptadas para processamento e obtenção de resultados. O presente trabalho, utilizando regiões intergênicas extraídas do IntergenicDB, (i) verificou o desempenho de ferramentas computacionais de predição de promotores disponíveis na internet; (ii) com o uso das ferramentas computacionais, apresenta uma análise comparativa de regiões intergênicas de linhagens de E. coli (comensal e patogênicas), procurando relacionar a estrutura dos promotores com a capacidade patogênica e (iii) o desenvolvimento da integração de ferramentas de análise de sequências ao IntergenicDB através da criação de um web service.
Keywords: Escherichia coli; Bioinformática; DNA; RNA polimerase; Bioinformatics; RNA polymerases